A manufacturing bottleneck case study trough the theory of constraints and computational simulation of the proposed bottleneck solution - Lemes Leite Barbosa, Gustavo; Cooper Ordoñez, Robert Eduardo; Anholon, Rosley; Sanchez, Mauricio Andrés (Brazilian Journal of Operations & Production Management, 2018)
In 2016, the Brazilian pet industry had revenue of R 18.9 billion and ranked third place worldwide. Thus, it is a sector that is always looking for enhancements in its productivity levels. Based on the previous statements, a case study was conducted in a selected company of the pet care business, with the goal to augment its monthly revenue, identify the bottleneck that impedes reaching this goal, and proposed solutions to bring the production and loading fluxes of merchandise to its optimal state, making the company’s revenue also optimal. The classical tools of the theory of constraints were used in this analysis. The first step was to obtain the undesirable effects of the process to define the bottleneck. After that, some injections were proposed as solutions to eliminate the undesirable effects and bring the production and loading model of the company to its full state. Finally, by means of a computational tool, the current situation of the company (with the bottleneck), and the situation in a virtual state (without the bottleneck) were simulated and compared, showing the potential of the found solution.